Sustainability of Tourism and Economic Development in Three Religious Tourism Destinations: The Critical Role of Fossil Fuel Energy on Air Pollution and Human Health - Bildirici, Melike; Ersin, Ozgur Omer (MDPI, 2025)
The study examined the relations and Granger causality among environmental pollution, air quality, life expectancy, religious tourism, petroleum consumption and economic growth in three countries, Italy, Saudi Arabia and T & uuml;rkiye, three countries with a prominent role of religious tourism, given the high shares of religious tourism revenues in their economies and due to pilgrimage-type religious tourism activities in total tourism activities. The study employed a yearly sample of 1975-2019 and novel Fourier-augmented vector autoregressive and Fourier Granger causality tests, under the structural breaks in the data. The findings indicate negative effects on environmental pollution and air quality from tourism in addition to such effects on life expectancy in all countries analyzed, and in this relation, fossil fuel consumption in these nations and its acceleration with tourism play crucial roles. These effects are amplified by economic growth coupled with tourism revenues that go in hand with high fossil fuel consumption, which further worsen the impacts on the environment. In the causality testing stage, the results determined unidirectional causality from tourism, fossil fuel energy consumption, and economic growth to both carbon dioxide emissions and to particulate matter 2.5. These effects are also reinforced by feedback effects between air pollution and life expectancy, which enhance the effects on both environment and air quality. These findings are used to suggest important policy recommendations, among which, the reduction in high dependency on fossil fuel in the energy mix is most central. Equally, policies are suggested to encourage sustainable tourism to reverse the adverse effects on health, environmental degradation and worsened air quality in these nations.
Keywords: environmental sustainability; sustainable tourism; air quality; health; sustainable development; environmental economics; fossil-fuel consumption; economic growth; Fourier; causality; CO2 EMISSIONS; CLIMATE-CHANGE; CONSUMPTION; PANEL; IMPACTS; GROWTH; PILGRIMAGES; HYPOTHESIS; ARRIVALS; QUALITY; Science & Technology - Other Topics; Environmental Sciences & Ecology